APLIKASI BEBERAPA DOSIS TRICHO-ECENG TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI (Capsicum annuum L.) PADA MEDIUM GAMBUT - Yuyun Penzi; Fifi Puspita; Adiwirman ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research is to determine the effect of multiple doses Tricho-hyacinth and get the best doses for the growth and production of chili (Capsicum annuum L.) on peat medium and to see the relationship between variables. This research was conducted at the experimental (House Kassa) Faculty of Agriculture, University of Riau Kelurahan Simpang Baru Km 12.5 Kecamatan Tampan Pekanbaru. This research was conducted from January to Mai 2014. This research was done experimentally with completely randomized design (CRD), which consists of 5 treatments and 4 replications, so that acquired 20 units of the experiment, each experimental unit consisted of two samples plant, so there were 40 samples plant. The treatment were Tricho-hyacinth dosis, K0: 0 g/polybag (0 ton/ha), KI: 80 g/polybag (2675.5 kg/ha), K2: 160 g/polybag (5351.2 kg/ha) , K3: 240 g/polybag (8026.8 kg/ha), K4: 320 g/polybag (10.702 kg/ha). The results obtained by analysis of variance followed by honesly test difference significant at the 5% level. To see the relationship between variables test. The parameters observed were plant height, height of dichotomous, stem diameter, crown width, flowering age, harvesting age, length of fruit and diameter, weight per fruit and fruit weight per plant. The giving of Tricho-hyacinth with various doses giving real effect to the crown width, fruit length and diameter chilies. The treatment Tricho-hyacinth dose of 320 g/polybag or 10.702 kg/ha gives the highest value of the fruit length and diameter red chilies compared with no treatment. Keyword : Capsicum annuum L., Tricho-hyacinth and Peat Medium